"Symbolic significance in the abstract art of the artists (Kandinsky and Mondrian) And a reflection on postmodern arts to enrich the field of design enrich the field of design" - Marwa Mohamed (Journal of Architecture, Art & Humanistic Science, 2019)
Research Summary: The new movements in the history of human thought are an expression of the contemporary style of the thought of that era; it gives new features to the identity of the human being. Every movement of modern creativity is intended to develop the ways of thinking towards life, existence, material objects and changing it by work and behavior and How can use new design formulations be derived from the symbolic significance of abstract art to create solutions for innovative designs and their role in design according to abstract art movements, which widens the designer's perception in the light of innovative arts to achieve positive values for the designer? The research aims at enriching new experimental entrances using computer programs through the symbolic significance of abstract art and enriching the designer's thought by extracting new design formulations which widens the designer's perception in the light of postmodern art. The research assumes that the designer can benefit from drawing innovative formulations through the symbolic significance of abstract art Using computer software which expands the designer's perception.key words :Symbolism - abstract art - modernitySearch Goal: The research aims at enriching postmodern art to create new formulations through symbolism, and enrich the designer's thought by drawing new formulations through abstract art, which expands the designer's perception.research importance:Drawing new formulations and designs through the symbolic significance of abstract art and linking it to postmodern art to create solutions for new designs.Research hypotheses:- The research assumes that the designer can benefit from abstract formulations of the symbolic significance of abstract art and its connection with postmodern arts to enrich the field of postmodern art.search limits:The objective boundaries of research focus on drawing abstract formulations from abstract art to enrich functional design.Research Methodology:The research follows the extrapolation method, descriptive analytical approach.-References:- Attieh, Mohsen, The Critical Experience in Fine Arts, The World of Books in Cairo 2011, 69- Al-Bahnasi, Afif, "From Modernity to Postmodernism in Art", Dar al-Kitab al-Arabi, Damascus Cairo, First Edition, 1997, p 235.